2016
DOI: 10.1190/int-2016-0021.1
|View full text |Cite
|
Sign up to set email alerts
|

Combining surface-wave phase-velocity dispersion curves and full microtremor horizontal-to-vertical spectral ratio for subsurface sedimentary site characterization

Abstract: We compute seismic velocity profiles by a combined inversion of surface-wave phase-velocity dispersion curves together with the full spectrum of the microtremor horizontal-to-vertical (H/V) spectral ratio at two sediment-covered sites in Germany. The sediment deposits are approximately 100 m thick at the first test site and approximately 400 m thick at the second test site. We have used an extended physical model based on the diffuse wavefield assumption for the interpretation of the observed microtremor H/V s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Piña-Flores et al 2016), but this non-uniqueness can be reduced significantly by inverting these measurements jointly, due to their complementary sensitivity (e.g. Arai & Tokimatsu 2004;Parolai et al 2005;Zor et al 2010;Dal Moro 2011;Piña-Flores et al 2016;Lontsi et al 2016;Spica et al 2018a).…”
Section: -D J O I N T I N V E R S I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Piña-Flores et al 2016), but this non-uniqueness can be reduced significantly by inverting these measurements jointly, due to their complementary sensitivity (e.g. Arai & Tokimatsu 2004;Parolai et al 2005;Zor et al 2010;Dal Moro 2011;Piña-Flores et al 2016;Lontsi et al 2016;Spica et al 2018a).…”
Section: -D J O I N T I N V E R S I O Nmentioning
confidence: 99%
“…Piña-Flores et al 2016). Independent information, such as surface wave dispersion (Scherbaum et al 2003;Piña-Flores et al 2016;Lontsi et al 2016) or H/V measurements recorded at different depths (Lontsi et al 2015;Spica et al 2017b) or locations (Perton et al 2017) all provide opportunities to reduce this non-uniqueness. Additionally, Perton et al (2017) suggested that the H and V components could be considered independently to assess the reliability of H/V and to characterize properties of the noise field illumination.…”
Section: Introductionmentioning
confidence: 99%
“…Sánchez-Sesma et al (2011) used the diffuse field assumption (DFA) to link the H/V of the autocorrelated signal (i.e., the directional energy densities in Perton et al, 2009) to the ratio of the imaginary parts of the 1D Green's functions. This formulation naturally allows for inversion of the structure at a site, and the inversion of the full spectrum of the H/V ratio has emerged as a powerful technique that has been applied to diverse data sets and geological settings (Salinas et al, 2014;Spica, Caudron, et al, 2015;Lontsi et al, 2015Lontsi et al, , 2016Rivet et al, 2015;García-Jerez et al, 2016;Piña-Flores et al, 2016;Perton et al, 2017;Wu et al, 2017). It has also proven its potential to give a reliable velocity model of the shallow subsurface using shallow borehole observations from the G-array .…”
Section: Introductionmentioning
confidence: 99%
“…Constraining the inversion by adding observations from sensors at depth significantly reduces the possible range of parameters (Lontsi et al 2015). Starting with an accurate first guess-as, for example, a guess obtained from an independent measurement such as a dispersion curve (Scherbaum et al 2003;Piña-Flores 2015;Lontsi et al 2016)-allows more rapid convergence. Although the Deltares-NAM model exists, our goal is to provide independent measurements in our analysis to test the validity of the method.…”
Section: Inversionmentioning
confidence: 99%
“…This capability is of particular interest in geotechnical engineering, seismic exploration, and engineering seismology. To date it has only been applied to limited data sets and geological settings (Salinas et al 2014;Spica et al 2015;Lontsi et al 2015;Piña-Flores 2015;Rivet et al 2015;Lontsi et al 2016;García-Jerez et al 2016;Piña-Flores et al 2016;Perton et al 2017). While these initial results are promising, there is still a need to explore the potential of the method and to validate the results against independent information.…”
Section: Introductionmentioning
confidence: 99%